Reflections of Political Changes in the Tharu Literary Writings (Voice: A Biannual & Bilingual Journal, 2025)
The literature of every language reflects society, people, and time in various ways. Tharu-language literature reflects different dimensions of Tharu life across time, despite having a comparatively shorter history than the major languages of Nepal. One of the main reasons why Tharu literature developed later is that Tharu people were deprived of access to education due to political and social reasons. Additionally, economic and geographical factors also played a significant role in hindering the Tharu people’s access to education. This research paper aims to explore how political changes in Nepal have been depicted in Tharu literature and how it has been influenced by the political shifts following the establishment of democracy in 1951 (2007 BS). The paper also examines whether political causes or changes have contributed to the development of Tharu literature. For this qualitative research, major Tharu literary works from the establishment of democracy to the present federal republic political system have been studied and analyzed. While the research primarily relies on library-based data analysis, consultations with prominent Tharu litterateurs were also conducted via available channels. The paper concludes that, although Tharu literature has not flourished to the same extent as literature in other languages, it does reflect political changes along with other pressing social and ethnic issues.